Literacy of Virtual Era Democracy in Al-Ma'soem Islamic Boarding School Sumedang Regency: UNPAD Community Service - Suwandi Sumartias (Universitas Serang Raya, 2021)
Abstract Since the 1998 reformation, the freedom of expression and political participation of citizens has been real and dynamic. Understanding and awareness of the importance of democracy as political education, especially in the Virtual Age, is increasingly becoming a challenge. The Santri, as the next generation, have a strategic role in the continuation of democratization in Indonesia. The method of activities on Virtual Era Democracy Literacy is carried out through the Online method with Problem Based Learning and Brainstorming techniques, through assistance of Community Service Program. The results of the activity show that the Literacy of Virtual Era Democracy provides benefits in increasing insight and understanding of democracy, especially in the virtual era. The Santri felt happy and enthusiastic about this activity, because online experiences provided a new atmosphere in the digital era. Changing the attitudes and new behavior in the digital domain regarding democracy need to be discussed continuously as an adaptation to new habits. Key Word: Literation, democracy, virtual , santri